Aprendizagem em redes de cooperação: estudo de caso envolvendo farmácias e drogarias na cidade de Maringá-PR - Padial, Rafael Bayouth (2009)
Through a case study of pharmacies and drugstores, organized independently owned network, located in the city of Maringa-PR. This study aimed to analyze the process of organizing work in networks and thus a new cross-organizational structure, called by Engestrom (2001), like as co-configuration, this environment conducive to raising the potential for learning, represent in fact an area of building knowledge. Based on the Activity Theory and its assumptions, the activity system, with group activities interpretive interaction, was taken as reference the learning process through the cycle of expansive learning has seven stages: questioning, analyzing , modeling a new solution, examining the model, reflecting on the process and building a new practice, the process by trying to answer such questions. Why learn? How do you learn? What is learned? Who learns? This is a qualitativedescriptive research, using a triangulation of data sources. Secondary data came from newspapers in the region, home page of the institution, statute, internal communications, contracts and official letters. Interviews held on primary data consisted of semi-structured questionnaires with members of the network meetings monthly. As mediators symbolic and network characteristics, we identify common goals, factors linked to interaction (beliefs, values, identity, connectivity and power relationship), management tools and ultimately gain competitive potentiated the network model. The results indicate the presence of two consolidated collective practices, collective purchasing and advertising campaigns that provide learning for the members and extends to members of the entire network. Issues to facilitate the expansion process, linked to this daily contacts, belong to the same sector, average age of the members, length of stay, the market knowledge and reciprocal difficulties, on the other hand, the limiting factors are configured for high positions and individual interests, weakness of the sector and low power of sale. A future analysis of the same network is required, recognizing the process of expansive learn, caused by new difficulties and / or analyze other network of pharmacies entered at the same context.